AGAMA, MANUSIA DAN LINGKUNGAN SEBAGAI PONDASI DAYA TARIK WISATA DI OBJEK WISATA PURA TIRTA EMPUL, TAMPAK SIRING, GIANYAR, BALI - I Made Trisna Semara, ST., M.Par (Jurnal Ilmiah Hospitality Management, 2014)
The purpose of the research is to know the factors that become the foundation of a touris attraction in Tirta Empul Temple. The benefit of this research is to organize a tourism region towards sustainable tourism. The research use qualitative method and quantitative descriptive analysis technique. The result of the research is Tirta Empul tourism has good foundation and friendly tourism. It supports the development of tourism in the future. Tirta Empul tourism foundation can be seen from the three factors. That can be seen from the religious, human and environmental. These faktors is a dynamic entity, complementary and not precede each other. This is the secret of balance tourism development in Tirta Empul.